PERAN UNIT PELAYANAN TERPADU PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (UPT P2TP2A) DALAM MENDAMPINGI ANAK KORBAN KEKERASAN SEKSUAL - Anton Aulawi; Miratussholihat . (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2024)
The Integrated Service Unit of the Integrated Service Center for the Empowerment of Women and Children (UPT P2TP2A) Serang Regency is an institution under the auspices of the Office of Family Planning for the Empowerment of Women and Children (DKBP3A) Serang Regency. UPT P2TP2A is an institution engaged in the social and legal fields. This study aims to determine the extent of the role of UPT P2TP2A in assisting Children Victims of Sexual Violence in Serang Regency. The method used in this study is a qualitative research in which the results of the findings in this study will be analyzed and described in detail and clearly. Cases of sexual violence against minors are still common in Serang Regency, seen from the data on cases of sexual violence which are increasing every year. To increase legal awareness of the community to be further improved. Extension programs that are considered to be able to prevent an increase in the number of sexual violence against children can be more effective. Basically, the role of UPT P2TP2A Serang Regency is in accordance with regulations on child protection and other implementing regulations. The obstacles that the researchers encountered were human resources, lack of legal education and the lack of parental roles.